Concise Review: Bioprinting of Stem Cells for Transplantable Tissue Fabrication - Leberfinger, Ashley N. (Stem Cells Transl Med, 2017)
Bioprinting is a quickly progressing technology, which holds the potential to generate replacement tissues and organs. Stem cells offer several advantages over differentiated cells for use as starting materials, including the potential for autologous tissue and differentiation into multiple cell lines. The three most commonly used stem cells are embryonic, induced pluripotent, and adult stem cells. Cells are combined with various natural and synthetic materials to form bioinks, which are used to fabricate scaffold‐based or scaffold‐free constructs. Computer aided design technology is combined with various bioprinting modalities including droplet‐, extrusion‐, or laser‐based bioprinting to create tissue constructs. Each bioink and modality has its own advantages and disadvantages. Various materials and techniques are combined to maximize the benefits. Researchers have been successful in bioprinting cartilage, bone, cardiac, nervous, liver, and vascular tissues. However, a major limitation to clinical translation is building large‐scale vascularized constructs. Many challenges must be overcome before this technology is used routinely in a clinical setting. Stem Cells Translational Medicine 2017;6:1940–1948